Performance Management Analysis of the Forum for Religious Harmony in Resolving Conflict and Maintaining Religious Harmony in South Tangerang City - Slamet Suwanto; Ngadisah; Nurliah Nurdin; Andi Pitono (International Journal of Science and Society, 2020)
This study aims to analyze the performance management of the Religious Harmony Forum, from now on referred to as FKUB, in maintaining interfaith harmony in the city of South Tangerang. This study used a qualitative approach with descriptive methods by conducting observations and interviews to collect data. In this study, it was found that FKUB South Tangerang City was not optimal in carrying out its functions and duties because it did not have good performance management. This can be seen from indicators, among others, there are still many people in South Tangerang City who do not know about the Tangsel FKUB and feel the benefits of the organization's existence, the Tangsel FKUB does not have a clear vision, mission and objectives, has not received adequate funding from the Tangsel City Government and has never carried out training for administrators. Therefore FKUB South Tangerang City needs to improve performance by using Armstrong performance management and Balance Scorecard (BSC).